Guided Note-Taking Strategy in Strengthening Students' Listening Skills - Setia Permana, Yulia; Cunandar, Dadang (LPPM Universitas Advent Indonesia, 2025)
This study explores using a guided note-taking strategy to address the issue of low listening skills among students. The primary aim is to evaluate the effectiveness of this strategy in strengthening listening skills. Conducted as qualitative research using a descriptive method, the study involved a school principal, classroom teachers, and three fourth-grade students as informants. Data collection techniques included interviews and document analysis. The study identifies several factors contributing to students' low listening skills, including limited concentration, insufficient understanding, weak memory retention, low motivation, and hearing impairments. Teachers sought to address these challenges by implementing the guided note-taking strategy. The findings suggest that this approach fosters improved listening skills through structured, easily applied steps.